2021
DOI: 10.1002/kjm2.12387
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA CCAT1 downregulation increases the radiosensitivity of non‐small cell lung cancer cells

Abstract: This study aims to investigate if the radiosensitivity of non-small cell lung cancer (NSCLC) cells can be regulated by long noncoding RNA (lncRNA) colon cancer associated transcript1 (CCAT1). CCAT1 was detected by quantitative reverse transcriptionpolymerase chain reaction (qRT-PCR) in NSCLC cells (A549, H1299, SK-MES1, H460, and H647) and human bronchial epithelial cells (16HBE). H460 and A549 cells were then selected for the determination of CCAT1 expression after exposure to radiation (0, 2, 4, 6 Gy) at dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The roles of lncRNAs in the efficacy of radiotherapy in non-surgically treated patients with advanced NSCLC are also gradually attracting attention. Wang et al reported that the expression of the lncRNA CCAT1, which is highly expressed in NSCLC cells, was down-regulated after irradiation, and its knockdown inhibited the mitogen-activated protein kinase pathway, which increased the radiosensitivity of NSCLC cells [22], while Ma et al demonstrated that the lncRNA LINC00460 can promote gefitinib resistance in NSCLC cells by sponging miR-769-5p to modulate EGFR [23]. The radiation resistance of lung cancer cells has long been a source of frustration for the field of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The roles of lncRNAs in the efficacy of radiotherapy in non-surgically treated patients with advanced NSCLC are also gradually attracting attention. Wang et al reported that the expression of the lncRNA CCAT1, which is highly expressed in NSCLC cells, was down-regulated after irradiation, and its knockdown inhibited the mitogen-activated protein kinase pathway, which increased the radiosensitivity of NSCLC cells [22], while Ma et al demonstrated that the lncRNA LINC00460 can promote gefitinib resistance in NSCLC cells by sponging miR-769-5p to modulate EGFR [23]. The radiation resistance of lung cancer cells has long been a source of frustration for the field of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of CCAT1 arrests cells at G2/M, which is believed to be the most radiosensitive moment for cells, and further promotes radiation-induced γH2AX expression, a DNA damage marker. Silencing CCAT1 may also block MAPK signaling pathways and decrease p-p38/p38, p-ERK/ERK, and p-JNK/JNK [ 33 ].…”
Section: Involvement Of Lncrnas In Radiobiological Processesmentioning
confidence: 99%